Evaluation of the use of botulinum toxin type A for strabismus regression: a systematic literature review (Research, Society and Development, 2022)
Botulinum toxin (BT) presents itself as a less invasive alternative for the correction of strabismus, acting by the high affinity for cholinergic synapses, which causes a blockage of acetylcholine release. Such application, consequently, causes a lower chemical-neural receptivity, reducing muscle responsiveness to contracture, not causing, however, complete paralysis. Through this mechanism, the injection of botulinum toxin type A (TBA) into the extraocular muscles allows the alteration of ocular alignment creating a temporary paralysis, producing an overcorrection of the strabismus in which a shortening of the antagonist muscle is induced. Histologically, a change in sarcomere density may occur, which favors permanent ocular alignment. In a partial analysis, several authors report good results with the use of TBA in the treatment of different presentations of strabismus. There are several classifications of indication, expected effects, and adverse effects through the procedure, which must be considered upon patient admission. Thus, botulinum toxin, injected intramuscularly, binds to terminal receptors found in motor nerves, acting by blocking the release of acetylcholine in the presynaptic terminal, deactivating fusion proteins, which prevents the release of acetylcholine in the synaptic cleft, which does not allow depolarization of the postsynaptic terminal, blocking muscle contraction by temporary chemical denervation.